Aspects of the socio‐economic situation of disabled people in Russia - D.V. Nekipelova (Векторы благополучия: экономика и социум, 2025)
The article analyzes the socio‐economic status of disabled people in Russia, their integration into society and employment issues. The article considers the main causes of disability, the dynamics of the number of disabled people in general and by groups. The key aspects are reflected, including the legal basis for support, accessibility of the environment, education, employment, income level and structure of expenses of households consisting of disabled people. Particular attention is paid to the issues of employment of citizens with disabilities, their low level of participation in the labor force along with the high level of unemployment are noted, the main barriers that determine such dynamics are systematized. It was revealed that despite the decrease in the total number of employed disabled people, the share of income from employment is growing, from self‐employment. The importance of state programs and legislative initiatives aimed at improving the quality of life of disabled people, as well as the need to develop inclusive practices is emphasized. The article points out the need for further development of an accessible environment, advanced training of disabled people and creation of incentives for employers. The author emphasizes the importance of a comprehensive approach to solving the problems of the disabled and calls for further research and active actions on the part of the state and society. The material will be useful for researchers, representatives of government bodies and public organizations dealing with issues of social protection of the disabled.